FOSTERING ENGLISH VOCABULARY ACQUISITION THROUGH THE "KNOW YOUR DICTIONARY" GAME - Fitriyah ,; Rohmani Nur Indah (Lingua, 2022)
Vocabulary mastery is the most critical element in learning English, and it can be obtained by applying games in teaching-learning activities designed for millennial teens. This study aims to identify whether the eight-grader students taught using the "Know Your Dictionary" game had higher vocabulary mastery than those who did not. Using a quasi-experimental design, the study was conducted on the eighth grade of Junior High School of Ma'arif 2 Pamekasan. It had two groups to be investigated; they were A class as experimental group and B class as the control group. The instruments of this study were tests and documentation. The study verified Wright's theory that students could foster their vocabulary through games. The research results indicate a significant impact of treatment on the students' vocabulary mastery. The students given treatment using the "Know Your Dictionary" game had higher vocabulary mastery than those taught conventionally. The experimental group's post-test results are proven to be higher than their pre-test scores and those of the control group. It confirms that the game effectively fostered the students' vocabulary mastery